A reception perspective on client-agent interactions in the DiaBiz corpus of spoken Polish - Mikołaj Deckert; Anna Cichosz (Ibérica)
This paper introduces the DiaBiz corpus (Pęzik et al., 2022) – a spoken corpus of call-centre dialogues in Polish – and discusses the findings of a reception experiment (N=100) exploring some of the characteristics of the language data in the corpus. Given that the conversations were recorded specifically for the corpus rather than being authentic exchanges extracted from real-life business contexts, we first offer evidence on how the DiaBiz dialogues are experienced and evaluated by language users along a range of reception parameters: cognitive load, absorption, comprehension as well as naturalness. The second main aim is to further nuance the account by comparing the experience of listening to the recordings of DiaBiz dialogues vs. reading their transcripts.